Management information systems : - Laudon, Kenneth C. (Pearson/Prentice Hall, 2006)
For sophmore, junior, senior, and MBA-level MIS and Information Systems courses. These authoritative authors continue to define the MIS course by integrating coverage of essential new technologies, their applications, and their impact on managerial decisions.